THE EFFECT OF 4P ON THE DECISION TO VISIT AMPERA 2 TAK VETERAN'S RESTAURANT BINTARO, JAKARTA SELATAN - Heny Ratnaningtyas; Nurbaeti Nurbaeti; Fetty Asmaniati; Amrullah Amrullahi (Universitas Islam Lamongan, 2022)
This study aims to determine the effect of product, price, business location, promotion on consumer visiting decisions. This research uses multiple regression analysis method. The sample of this research is 100 people. The sampling technique used was accidental sampling technique. The results showed that partially product, price, business location and promotion had a significant effect on visiting decisions. This is because Ampera 2 Tak Veteran Bintaro Restaurant displays attractive, clean and tidy Sundanese food products at affordable prices and strategic business locations and promotions carried out by consumers through Instagram or Facebook. In this research, it is hoped that Ampera 2 Tak Veteran Bintaro Restaurant can maintain and increase consumer interest in visiting Sundanese restaurants